2021
DOI: 10.1007/s00395-021-00896-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of remote ischaemic conditioning on infarct size and remodelling in ST-segment elevation myocardial infarction patients: the CONDI-2/ERIC-PPCI CMR substudy

Abstract: The effect of limb remote ischaemic conditioning (RIC) on myocardial infarct (MI) size and left ventricular ejection fraction (LVEF) was investigated in a pre-planned cardiovascular magnetic resonance (CMR) substudy of the CONDI-2/ERIC-PPCI trial. This single-blind multi-centre trial (7 sites in UK and Denmark) included 169 ST-segment elevation myocardial infarction (STEMI) patients who were already randomised to either control (n = 89) or limb RIC (n = 80) (4 × 5 min cycles of arm cuff inflations/deflations)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…In the CONDI-2/ERIC-PPCI trial, remote ischaemic perconditioning neither reduced infarct size (as assessed by 48-h troponin release or by CMR [n = 110]) nor improved the primary clinical endpoint (composite of cardiac mortality and heart failure hospitalisation at 12 months) [13,18]. However, previous RIC studies have suggested the presence of discordant effects on infarct size and clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the CONDI-2/ERIC-PPCI trial, remote ischaemic perconditioning neither reduced infarct size (as assessed by 48-h troponin release or by CMR [n = 110]) nor improved the primary clinical endpoint (composite of cardiac mortality and heart failure hospitalisation at 12 months) [13,18]. However, previous RIC studies have suggested the presence of discordant effects on infarct size and clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In some previous studies undertaken during the acute phase of STEMI, adjunctive RIC (with primary percutaneous coronary intervention [P-PCI]) attenuated infarct size and/or reduced the incidence of LV systolic dysfunction and major adverse cardiac events, albeit not consistently [1,5,9,14,31,32,42,56,60]. However, in the largest-scale randomised trial (CONDI-2/ERIC-PPCI, n = 5401), RIC failed to reduce infarct size or improve 12 month clinical outcomes (cardiac mortality/heart failure hospitalisation) [13,18].…”
Section: Introductionmentioning
confidence: 99%
“…Since oedema formation is highly dependent on the size of infarction, 51 whether smaller infarcts or different AAR display the same time‐dependent oedema pattern remains to be assessed in order to standardize the best timing for CMR analyses 14 . Interestingly, we have developed a model with infarctions within the order of magnitude of those obtained in the era of modern revascularization procedures (around 16% LV) ensuring an enhanced translatability to the clinical arena of the obtained results 52,53 . Yet, it is important to consider that large infarcts may overestimate cardioprotective interventions, likely contributing to the failure to translate successful and novel experimental strategies to the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…14 Interestingly, we have developed a model with infarctions within the order of magnitude of those obtained in the era of modern revascularization procedures (around 16% LV) ensuring an enhanced translatability to the clinical arena of the obtained results. 52,53 Yet, it is important to consider that large infarcts may overestimate cardioprotective interventions, likely contributing to the failure to translate successful and novel experimental strategies to the clinical setting. However, despite a comparable degree of myocardial damage, MVO is mildly present after 60 min of ischemia and markedly increased from 90 min of ischemia onwards.…”
Section: Discussionmentioning
confidence: 99%
“…A prospectively pre-specified sub-analysis of the CONDI-2/ERIC-PPCI trial, assessing changes in cardiovascular magnetic resonance (CMR) parameters, did not demonstrate statistically significant differences between the control and intervention groups, however an improvement in Left Ventricular Ejection Fraction (LVEF) and Microvascular Obstruction (MVO) in the RIC group was demonstrated on the acute scan when specifically assessing Left Anterior Descending (LAD) STEMI ( 8 ). The results are consistent with previous findings from our research group, whereby a modest short-term improvement in left ventricular (LV) function was demonstrated in high-risk patients treated with RIC ( 9 ).…”
Section: Introductionmentioning
confidence: 99%